The Epstein-Barr virus-induced Ca2+/calmodulin-dependent kinase type IV/Gr promotes a Ca(2+)-dependent switch from latency to viral replication. - Chatila, T (1997)
The switch from latency to viral replication in Epstein-Barr virus (EBV)-transformed human B cells is mediated by Zta, the protein product of immediate-early EBV gene BZLF1. BZLF1 transcription is normally suppressed in EBV-transformed B cells but can be induced in some cell lines upon ligation of surface immunoglobulin by mechanisms that include the activation of Ca(2+)-dependent signaling pathways. The multifunctional Ca2+/calmodulin-dependent kinase type IV/Gr (CaMKIV/Gr) is normally absent in primary human B cells, but its expression is induced by the EBV oncoprotein LMP1 in the course of B-cell growth transformation by EBV. In this study, we demonstrate that activated CaMKIV/Gr induces transcription from the BZLF1 promoter and upregulates the expression of Zta in permissive cells. Transcriptional activation of the BZLF1 promoter by CaMKIV/Gr is dependent on the CREB/AP1 binding element ZII and is greatly augmented by the Ca2+/calmodulin-dependent phosphatase calcineurin. These results outline a virus-regulated mechanism involving CaMKIV/Gr which promotes transition from latency to productive viral replication in response to Ca(2+)-mobilizing extracellular signals.